Genetic manipulation of the cell wall composition of sugarcane - Bekker, Jan P. I. (Stellenbosch : University of Stellenbosch, 2007)
In order to understand and manipulate carbon flux to sucrose one needs to consider not only its biosynthetic pathways, but also the competing sinks for carbon in various parts of the plant and at different stages of development. The cell wall and sucrose is known to be the major sinks for carbon in young and mature tissues of sugarcane. UDP-Glucose is a central metabolite in the synthesis of both sucrose and most of the cell wall polysaccharides (including cellulose, hemicellulose and pectic polymers) and manipulation of the flux into either of the cell wall components could therefore cause an increase of flux toward one or more of the competing sinks. In the present study UDP-Glucose dehydrogenase (UGD) activity was chosen for down regulation as it catalyzes the rate limiting step in the biosynthesis of the precursors of both hemicellulose and pectin, a major competing sink for assimilated carbon. Transgenic sugarcane lines with repressed UGD activity showed significantly increased sucrose accumulation in all internodes which was highly correlated with reduced UGD activity. Sucrose phosphate synthase had increased activation which suggests an alteration in carbon flux toward sucrose. The reduction of carbon flux through UGD was compensated for by an increase in the activity of the myo-inositol oxygenation pathway (MIOP), an alternative pathway for the synthesis of cell wall matrix precursors. The increased activity of the MIOP resulted in increased total uronic acids and pentoses in the cell wall. Total cell wall glucose was also increased which is a further indication of altered carbon metabolism.